PENGELOLAAN POTENSI SUMBERDAYA PERIKANAN DI DUSUN TAMAN SEJARAH, DESA WAESALA, SERAM BAGIAN BARAT - Tuhumury, Julian; Tawari, Ruslan H. S.; Siahainenia, Stany R.; Nanlohy, Alberth Ch.; Noija, Donald (Pattimura University, 2023)
Taman Sejarah Hamlet is located in Waesala Village, Huamual Rear District, West Seram. It’s location by the coastline makes it an ideal spot for fishing activities. Most of it’s residents work as fishermen due to their easy access to the sea. However, the fishermen are currently facing a fish resource crisis, with a significant and decline in fish populations every year. Overfishing is one of the main factors causing this crisis. The lack of information and understanding among the fishermen about marine conservation means that fishing and management of marine resources cannot be properly measured or managed. The community service being carried out in Taman Sejarah Hamlet aims to provide enlightenment and positive contributions to the local fishing community about how to manage marine resources well and wisely.